2019
DOI: 10.1016/j.tranon.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A CRISPR Test for Detection of Circulating Nuclei Acids

Abstract: Emerging CRISPR-based nucleic acid detection shows great promise in molecular diagnosis of diseases. CRISPR-Cas12a can sensitively and specifically detect human papillomavirus (HPV) DNA in anal swabs. However, the current CRISPR-Cas12a system needs auxiliary and expensive equipment, which limit its application as a point-of-care (POC) diagnostic tool. This study aimed to develop CRISPR-Cas12a as a POC test to directly target plasma for circulating HPV DNA detection by immediately reading results with naked eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 17 publications
0
72
0
Order By: Relevance
“…In most of these platforms, a commercially available universal test strip, the HybriDetect-Universal Lateral Flow Assay Kit, was used. This dipstick was originally designed for qualitative or even quantitative rapid testing of proteins, antibodies or gene amplicons, but has been adapted to function in several LFA based CRISPR sensing methods ( Bai et al, 2019 ; Chang et al, 2019 ; Gootenberg et al, 2018 ; Kaminski et al, 2020 ; Mukama et al, 2020b ; Sullivan et al, 2019 ; Tsou et al, 2019 ). This platform offers a Streptavidine line as well as an antibody line that can capture anti-FITC coated AuNPs ( Fig.…”
Section: Crispr/cas Sensing In Poc Sensorsmentioning
confidence: 99%
“…In most of these platforms, a commercially available universal test strip, the HybriDetect-Universal Lateral Flow Assay Kit, was used. This dipstick was originally designed for qualitative or even quantitative rapid testing of proteins, antibodies or gene amplicons, but has been adapted to function in several LFA based CRISPR sensing methods ( Bai et al, 2019 ; Chang et al, 2019 ; Gootenberg et al, 2018 ; Kaminski et al, 2020 ; Mukama et al, 2020b ; Sullivan et al, 2019 ; Tsou et al, 2019 ). This platform offers a Streptavidine line as well as an antibody line that can capture anti-FITC coated AuNPs ( Fig.…”
Section: Crispr/cas Sensing In Poc Sensorsmentioning
confidence: 99%
“…Unlike PCR that requires ultra-purified buffer solutions, 44 , 45 one of the unique advantages of CRISPR-based detection is that the collateral cleavage process is not affected much by the presence of nucleases in bodily fluids. For example, numerous studies have shown the sensitive detection of nucleic acid samples in urine, 46 saliva, 17 and plasma 47 samples without stringent purification. However, to meet the requirements of “real-world” POC diagnostics, a nucleic acid concentration step may still be needed as the lysis process could result in the dilution and loss of target samples, especially when the viral load is low.…”
Section: Discussionmentioning
confidence: 99%
“…17,39 An advantage of the IMPACT chip compared to other detection apparatuses such as the SHERLOCK test strip is that it is a fully enclosed system without extra packaging need. 40,41 This is advantageous as the treated micropillars are sealed before molecular diagnostics. The reporter probes are immobilized within the channel, avoiding degradation issues from outside contaminants.…”
Section: Discussionmentioning
confidence: 99%